Some Do Not - Ford, Ford Madox (Saga Egmont, 2023)
Some Do Not... is a novel by Ford Madox Ford, first published in 1924. It is the first in the Parade\'s End series, which chronicles the life of a member of the British gentry before, during, and after World War I. In \'Some Do Not...\', Christopher Tietjens, a government statistician, and his friend Vincent Macmaster, an aspiring literary critic, are visiting the English countryside. Whilst there Tietjens meets a suffragette, Valentine Wannop. Although married, Tietjens is not happy, and a love affair with Valentine develops. An honorable and old fashioned man, Tietjen doesn\'t want to leave his wife, but whether that is to do with simple honor and loyalty, or because he moved up the social ladder when he married - is left up to the reader. His rules of honor and nobility also affect his stance towards the war, the horrors of which are explored in the novel, from outside the battlefield. In all, Some Do Not... shows that each individual character has their own motivations, despite the propaganda of the day painting the entire country of England as one of heroics and high morality.